Writing history in the Third Republic - DiVanna, Isabel (Cambridge Scholars Pub., 2010)
This book offers new insight to one of the most neglected periods of historiographical output: that of French historians between 1860 and 1914, a period often referred to as of positivistic historians or the école méthodique. Having sought to assert their independence from Germanic influence by emphasising the French element in their work, historians in the period comprised between 1860 and 1914 sometimes described their approach as positivistic and maintained that this was a distinctively Fr ...